SPECTROSCOPY AND ROCKWELL HARDNESS TO CHARACTERIZE THE DETERIORATION OF WOOD TREATED WITH NATURAL PRODUCT - Silveira, Amanda Grassmann da; Santini, Elio José; Talgatti, Maiara; Campos Cancian, Luciano; Trevisan, Rômulo; Baldin, Talita (Floresta, 2019)
The objective of study was to characterize wood deterioration in samples with conventional and natural treatments using Rockwell hardness and spectroscopy. Five acacia trees were used to make 70 samples, of which 20 were treated with tannin and 10 with a Copper Chrome Borate mixture (CCB), while 10 samples exposed to fungus received no treatment and 30 were used as unexposed controls. The specimens for preservative treatments were saturated with the solutions, using full cell pressure in autoclave. Shortly after the treatment, the samples were exposed to Pycnoporus sanguineus for 16 weeks, using the accelerated rot test. Then, deterioration was evaluated by spectroscopy and Rockwell hardness. CCB was the most suitable to preserve wood hardness, followed by treatments with 10 and 5% of tannin, and all treatments presented similar values indicating they produced similar effects. Medium infrared spectroscopy analysis indicated that the material treated with 5 and 10% tannin showed the greatest similarity to the spectra from control samples.